Numerical Simulation and Shear Capacity Study of a New Double-Steel-Plate Shear Wall - Xiaomeng Zhang; Qingying Ren; Jiaqi Wang; Ziao Liu; Xiao Yang (Advances in Civil Engineering)
This paper presents a new type of double-steel-plate shear wall. Through the finite element software, the stress and plastic strain of steel plate and concrete in different loading stages of the wall are analyzed, the mechanical properties and failure rules of the wall are revealed, and the failure mechanism of the wall is obtained. The comparison with the test results verifies the correctness of the finite element analysis. Through nonlinear finite element parameterization analysis, the composition of shear capacity of each composite wall is obtained. Based on the superposition theory, practical calculation formula of its shear capacity is given, and through a comparative analysis with simulation test results, the goodness-of-fit is satisfying.